Gas chromatographic analysis of the products from the gamma-induced reaction between H2 and CCI4 - Hild, Sigifredo Lorenzo D.; Molinari, Marcelo Antonio; Videla, G. J. (1973)
Fil: Hild, Sigifredo Lorenzo D. Comisión Nacional de Energía Atómica; Argentina